Analisis Nilai Ketidakrataan Jalan Ahmad Yani Kota Balikpapan Dengan Metode International Roughnes Index (IRI) Menggunakan Aplikasi Road Bump Pro - Ain, Mohamad Isram M; Sunarno, Sunarno; Respati, Sara Wibawaning; Nadhifah, Anisa (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2025)
Ahmad Yani Street is an arterial road that serves as a strategic route connecting school areas, shopping centers, industrial zones, and national strategic areas such as airports and ports. This road segment is constantly used by motorized vehicles at all times, bearing the load from these vehicles, which causes a decline in road conditions, both structural and non-structural. Therefore, periodic road condition assessments are necessary. These assessments are required for evaluation in road planning and maintenance for the future and can be carried out by evaluating the road surface condition. This study aims to determine the surface roughness condition and the appropriate treatment for Ahmad Yani Road using the International Roughness Index (IRI) method with the Road Bump Pro application, applied to three different vehicle types: sedan, SUV, and pick-up. Based on the survey results of the IRI values obtained using SUV, pick-up, and sedan vehicles, the average IRI values were 2.44 m/km, 2.69 m/km, and 2.42 m/km.. Keywords: Road Surface Condition, International Roughness Index, Road Bump Pro